Analysis of performance of Attitude & Heading Reference System (AHRS) motion sensor algorithms through Bluetooth Low Energy (BLE) in nRF52840 System-On-Chip (SOC) - Chung, Benjamin Zhi Yong (Nanyang Technological University, 2024)
This research report investigates the performance of three distinct motion sensor algorithms, namely NXP, Madgwick, and Mahony, implemented on the Nordic NRF52840 System-on-Chip (SOC) through Bluetooth Low Energy (BLE) communication. The study utilizes the Adafruit Feather Sense board as the experimental platform for evaluating the algorithms' efficacy in providing accurate motion tracking and orientation estimation.